Strategi Coping Anak Broken-home dalam Menghadapi Tekanan - Ananda Dwi Shepty Mi'rajtul Jannah; Evi Winingsih; Najlatun Naqiyah (Jurnal Bimbingan dan Konseling Ar-Rahman, 2025)
A broken-home refers to a family condition marked by disharmony, parental conflict, or separation that disrupts emotional stability and adaptation in children. University students from broken-home backgrounds often experience psychological pressures such as loneliness, loss of parental figures, and difficulties in regulating emotions. This study aims to describe the types of pressures encountered, the coping strategies employed, and the role of social support in helping students deal with these challenges. The research used a qualitative descriptive method. Data were collected through semi-structured interviews with four students from broken-home families. The results revealed that students used two main types of coping strategies: problem-focused coping through problem-solving efforts and seeking social support, and emotion-focused coping through self-control, reflection, and positive activities such as writing or praying. Peer support emerged as a crucial factor that strengthened resilience and promoted self-acceptance among participants. This study suggests that guidance and counseling services in higher education should focus on reinforcing adaptive coping strategies, fostering supportive social environments, and developing psychoeducational programs to enhance resilience and psychological well-being among students from broken-home families. ____________________________________________________________Keluarga broken-home merupakan kondisi di mana keharmonisan keluarga terganggu akibat konflik, perceraian, atau ketidakhadiran salah satu orang tua, yang berdampak pada kestabilan emosional dan kemampuan adaptasi anak. Mahasiswa yang berasal dari keluarga broken-home sering menghadapi tekanan psikologis seperti kesepian, kehilangan figur, dan kesulitan dalam mengelola emosi. Penelitian ini bertujuan untuk mendeskripsikan bentuk tekanan yang dialami, strategi coping yang digunakan, serta peran dukungan sosial dalam membantu mahasiswa menghadapi tekanan tersebut. Pendekatan penelitian yang digunakan adalah metode kualitatif  deskriptif. Data dikumpulkan melalui wawancara semi-terstruktur terhadap empat mahasiswa dari keluarga broken-home. Hasil penelitian menunjukkan bahwa mahasiswa menggunakan dua bentuk strategi coping utama, yaitu problem-focused coping melalui upaya penyelesaian masalah dan pencarian dukungan sosial, serta emotion-focused coping melalui pengendalian diri, refleksi, dan kegiatan positif seperti menulis atau berdoa. Dukungan teman sebaya terbukti menjadi faktor penting yang memperkuat resiliensi dan menumbuhkan rasa penerimaan diri. Penelitian ini menyarankan agar layanan bimbingan dan konseling di perguruan tinggi lebih berfokus pada penguatan strategi coping adaptif, membangun lingkungan sosial yang suportif, serta mengembangkan program psikoedukasi untuk meningkatkan resiliensi dan kesejahteraan psikologis mahasiswa broken-home.